The image of Arabs in Mazedia religious texts (Journal of the College of Basic Education, 2025)
The image of Arabs in religious texts of non-Arabs is very different as contained in Arab texts, whether religious, historical or literary, In the books of legislation, jurisprudence, history and literature - Arabic - it appears to be sex above other races If these sources deliberately conceal facts that devalue Arabs as the authors of the Mohammadiyah letter, While the legislative, historical and moral sources of non-Arabs are abundant with many facts that shape the image of Arabs as seen and coexisted with them both before and after the occupation of their lands and this study merely highlights some of the disproportionate religious texts in which the image of Arabs is reflected, The overall picture of the Arab occupation of their regions is that the prophecies contained in their religious texts have always hoped to get rid of the yoke and injustice of the occupiers of their land and those who have caused the corruption of their religion.